Characterisation of heavy mineral sands and soils by radiometry and its use in mineral benefication and agriculture - De Villiers, Dawid (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Physics))--University of Stellenbosch, 2011.